Hot electron cooling in InSb probed by ultrafast time-resolved terahertz cyclotron resonance - Xia, CQ; Monti, M; Boland, J; Herz, L; Lloyd-Hughes, J; Filip, M; Johnston, M (American Physical Society, 2021)
Measuring terahertz (THz) conductivity on an ultrafast time scale is an excellent way to observe charge-carrier dynamics in semiconductors as a function of time after photoexcitation. However, a conductivity measurement alone cannot separate the effects of charge-carrier recombination from effective mass changes as charges cool and experience different regions of the electronic band structure. Here we present a form of time-resolved magneto-THz spectroscopy which allows us to measure cyclotron effective mass on a picosecond time scale. We demonstrate this technique by observing electron cooling in the technologically-significant narrow-bandgap semiconductor indium antimonide (InSb). A significant reduction of electron effective mass from 0.032 me to 0.017 me is observed in the first 200 ps after injecting hot electrons. Measurement of electron effective mass in InSb as a function of photo-injected electron density agrees well with conduction band non-parabolicity predictions from ab initio calculations of the quasiparticle band structure.